The effects of soleus fascicle length on muscle fatigability - Nguyen, Anh D.; Gray, Aubrey; Sawicki, Gregory; Franz, Jason R. (PeerJ, 2025)
Background Age-related deficits in Achilles tendon stiffness have been linked to shorter calf muscle operating lengths. These shorter lengths have the potential to precipitate higher requisite excitations and thereby an earlier onset of local fatigability in older adults. However, the connection between calf muscle operating lengths and muscle fatigability has yet to be systematically explored, even in healthy younger adults. Thus, the goal of this study was to establish a mechanistic pathway between soleus fascicle length, prescribed herein using changes in ankle joint angle, and muscle fatigue in a cohort of younger adults. Methods Participants performed repeated fixed-end calf muscle contractions to task failure in a computerized robotic dynamometer at two ankle joint angles to prescribe relatively shorter (i.e., 15° plantarflexion (PF15)) and longer (i.e., 15° dorsiflexion (DF15)) soleus fascicle lengths. Results On average, moving from DF15 to PF15 elicited 14% shorter muscle fascicle lengths, a roughly two-fold higher EMG rms amplitude, significant but modest reductions in EMG median frequency, and a 60% reduction in time to task failure (p-values < 0.05). These findings may have clinical relevance for mechanisms associated with higher metabolic costs and increased fatigability among older adults, who often operate their calf muscles at shorter fascicle lengths due to lesser Achilles tendon stiffness. As a roadmap for comparison and hypothesis generation, this study sets the stage for future work in older adults.
Keywords: Fatigue; Contraction; Biomechanics; Electromyography; Force